Development of Interactive Teaching Materials Based on Multiple Intelligences and Character: Pengembangan Bahan Ajar Interaktif Berdasarkan Multiple Intelligences dan Nilai Karakter - Rozhana, Kardiana Metha (Pedagogia : Jurnal Pendidikan, 2022)
The purpose of this research is to produce interactive teaching materials for Multiple Intelligences and character values in the basic concepts of Civics Elementary School which are interesting and valid (both in terms of implementation, effectiveness, and usefulness). This study uses research and development methods (Research and Development). The sample of this study was 44 students of the PGSD Study Program at Tribhuwana Tunggadewi University batch 2019/2020. Based on the results of the trial, the results obtained successively with a score of 93.2% for product validity, 89% for product implementation, 92% for product usefulness, 90% for effectiveness, and 90% for product attractiveness. From these results it can be concluded that these teaching materials can improve the cognitive abilities and attitudes of students in the Primary School Teacher Education Study Program